2017
DOI: 10.1080/10665684.2016.1262300
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Faculty of Color: Narratives about Entering the Academy

Abstract: The experiences of first-year, tenure-track faculty have been missing in the literature about new or junior faculty. Furthermore, the extant literature about new faculty does not offer a critical outlook on how oppressive institutional structures shape how first-year faculty of color approach faculty work. Drawing from analytical narratives, the authors reframe how doctoral student socialization and new-faculty support systems are discussed, especially pertaining to firstyear faculty of color. In doing so, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…These attitudes reflect color blindness and post-racial era thinking (Wilder et al, 2015). Institutions, however, can counteract this type of thinking by hosting social events and discussions about diversity and success to provide a welcoming environment for faculty of color (Cole et al, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…These attitudes reflect color blindness and post-racial era thinking (Wilder et al, 2015). Institutions, however, can counteract this type of thinking by hosting social events and discussions about diversity and success to provide a welcoming environment for faculty of color (Cole et al, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The lack of experienced faculty of color makes it difficult for new faculty of color to connect with colleagues and form mentoring relationships (Abdul-Raheem, 2016). Cole et al (2017) indicated that mentors help faculty of color acclimate to their institutional environments and offer guidance that teaches new faculty the ins and outs of the institution. It goes a long way in learning the institution's culture and learning the necessary steps for promotion and tenure.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent to the study at hand, explored the lives of pre-tenure faculty of color in educational leadership (n = 12) and learned many faculty of color experienced a "double consciousness" described as being necessary to navigate "the politics of the dominant White, male culture of their departments" while exploring their "personal racialized identities as a form of resistance to the status quo" (p. 131). Cole et al (2017) articulated personal narratives of three first-year faculty of color and emphasized the importance of peer and colleague groups, social media networks, and multiple forms of institutional support-including emails, coffee dates, and 5-min conversations-that greatly supported new faculty of color in tenure-track positions. Specific to faculty of color in higher education departments (n = 20), J. M. Johnson et al (2018) also found social networks to be valuable sources of support for faculty of color navigating PWIs.…”
Section: A Selective Literature Review Of Faculty Of Color In Academementioning
confidence: 99%
“…Reflection is an honored tradition in evaluation and evaluators are encouraged to reflect upon our practice (Kallemeyn, Hall, Friche, & McReynolds, 2015). Novice faculty have found that reflection, included within larger narrative inquiry research, can assist with the venture of grooming scholars into faculty (Cole, McGowan, & Zerquera, 2017). We encourage novice and seasoned evaluation educators alike, to not only familiarize themselves with teaching evaluation literature but also to systematically reflect upon their experiences as they develop and implement evaluation courses.…”
Section: Future Research and Concluding Thoughtsmentioning
confidence: 99%